Pain affects spouses too: Personal experience with pain and catastrophizing as correlates of spouse distress - Leonard, Michelle T (2006)
Chronic pain has adverse effects on individuals with chronic pain (ICPs) as well as their family members. Borrowing from an empathy model described by Goubert et al. (2005), we examined top-down and bottom-up factors that may be related to psychological well-being in the spouses of ICPs. A diverse community sample of 113 middle-aged spouses of individuals with chronic pain (ICPs) completed measures on pain severity and spouse pain catastrophizing (PCS-S; Cano et al., 2005). Results showed that almost half (48.7%) of spouses reported chronic pain themselves and that pain in the spouse accounted for within-couple differences on psychological distress. That is, in couples where only the ICP reported pain, ICP psychological distress was greater than their spouses. However, when both partners reported chronic pain, there was no significant difference in psychological distress between partners. Hierarchical regression analyses showed that spouse magnification catastrophizing was associated with depressive and anxiety symptoms, and that helplessness catastrophizing was associated with depressive symptoms for spouses of ICPs who also reported chronic pain but not for spouses of ICPs without chronic pain. The results are discussed in light of interpersonal processes that may affect spouses’ distress.